Microstructural evolution of spinodally formed Fe35Ni15Mn25Al25 - Baker, I.; Zheng, R.; Saxey, David; Kuwano, S.; Wittmann, M.; Loudis, J.; Prasad, K.; Liu, Z.; Marceau, R.; Munroe, P.; Ringer, S. (ELSEVIER Ltd, 2009)
The microstructural evolution of a b.c.c.-based, spinodally formed alloy Fe35Ni15Mn25Al25 has been studied as a function of annealing time at 550 °C using atom probe tomography and transmission electron microscopy, including energy-filtered imaging. The sizes, crystal structures, orientation relationships and compositions of the phases present were determined as a function of annealing time. The hardness showed complicated behavior as a function of annealing time, consisting of initial hardening, followed by softening and finally, by a rapid hardening behavior. The hardness is controlled both by the coarsening of the spinodally formed phases, and the precipitation and growth of ß-Mn structured particles. © 2009 Elsevier Ltd. All rights reserved.